MANAGEMENT OF THE HAEMOPHILIC PATIENT IN DENTISTRY AND CERVICOFACIAL SURGERY - Lidia Cureniuc; Emilia Pătrășcanu; Daniela Șulea; Emilia Bologa; Liviu-Vlad Hârtie; Carmen-Gabriela Stelea; Maria Paula Comanescu; Delia Hînganu; Victor-Vlad Costan; Cristina Popa; Oana Viola Bădulescu; Otilia Boișteanu (Romanian Society of Oral Rehabilitation, 2023)
In patients with haemophilia, any oral surgery carries the risk of prolonged and excessive bleeding. Close collaboration between haematologists and oral surgeons is necessary to prevent excessive bleeding. No procedure can be considered minor in a patient with haemophilia because of the serious potential consequences. Successful treatment protocols using systemic treatment, antifibrinolytic agents and local haemostatic measures are described in the current literature.